Greek New Testament manuscripts from Albania - LaFleur, Didier (New testament tools, studies and documents, 2018)
Front Matter -- Copyright Page /Didier Lafleur -- Acknowledgements /Didier Lafleur -- Abbreviations /Didier Lafleur -- Introduction /Didier Lafleur -- Greek Manuscripts from Albania: A Historical Background /Didier Lafleur -- Greek Manuscripts from Albania: A Historical Background /Didier Lafleur -- The Manuscripts /Didier Lafleur -- Albanian National Archives 1 (pl. 1) /Didier Lafleur -- Albanian National Archives 2 (pl. 2–3) /Didier Lafleur -- Albanian National Archives 4 (pl. 5–6) /Didier Lafleur -- Albanian National Archives 5 (pl. 7) /Didier Lafleur -- Albanian National Archives 10 (pl. 8) /Didier Lafleur -- Albanian National Archives 12 (pl. 9) /Didier Lafleur -- Albanian National Archives 15 (pl. 10) /Didier Lafleur -- Albanian National Archives 17 (pl. 11) /Didier Lafleur -- Albanian National Archives 19 (pl. 12) /Didier Lafleur -- Albanian National Archives 26 (pl. 13) /Didier Lafleur -- Albanian National Archives 29 (pl. 14) /Didier Lafleur -- Albanian National Archives 35 (pl. 15) /Didier Lafleur -- Albanian National Archives 38 (pl. 16) /Didier Lafleur -- Albanian National Archives 76 (pl. 17) /Didier Lafleur -- Albanian National Archives 79 (pl. 18) /Didier Lafleur -- Albanian National Archives 85 (pl. 19) /Didier Lafleur -- Albanian National Archives 92 (pl. 20) /Didier Lafleur -- Albanian National Archives 93 (pl. 21) /Didier Lafleur -- Albanian National Archives 98 (pl. 22) /Didier Lafleur -- Albanian National Archives, Fragment 7 (pl. 23) /Didier Lafleur -- Albanian National Archives, Fragment 12 (pl. 24) /Didier Lafleur -- Postscript /Didier Lafleur -- Numbering Concordance of the Greek Manuscripts from Albania /Didier Lafleur -- Common Codicological Features of Some Tirana Greek Manuscripts /Didier Lafleur -- A Non-Exhaustive List of Biblical and Non-Biblical Manuscripts Related to Albania and/or to Ἄνθιμος Ἀλεξούδης /Didier Lafleur -- Collations of the Three Different Editions of the Σκουριπέκης’ Chronicle (1887, 1892, 1901) /Didier Lafleur -- Plate Section /Didier Lafleur -- Back Matter -- Bibliography /Didier Lafleur.